FRESH WATER FISH AS A CAPITAL FR ESTABLISHUNG A FISH PROCESSING CENTER IN THE COMMUNITY OF MOROCALAN VILLAGE GLAGAH DISTRICT TO INCREASE HOUSEHOLD INCOME - Noer Rafikah Zulyanti; Sani Rusminah; Levia Inggrit Sayekti (SEAN Institute, 2023)
Morocalan Village is one of the villages in Glagah District. Most of the Morocalan villagers make a living as fish farmers. The problem in Morocalan Village is that it does not optimize the potential results in the village. Based on the results of discussions with the Morocalan village community, the following are solutions to solve the above problems: Increasing the income of the Morocalan Village community, by inviting the community to become entrepreneurs, Establishing a center for processing freshwater fish business, Making the processed freshwater fish into a superior village product that can be marketed in local, regional, and national markets. Cooperating with freshwater fish management companies, in order to increase production capacity. The purpose of holding this program is to form new entrepreneurs in Morocalan village, and to increase income from Morocalan village. The steps in the activity plan that we will do are, starting with exploring partner problems, continuing with finding solutions, and continuing with training, not only that, we will also form a sociopreneur group in Morocalan village, so that later a fish processing center will be formed. Morocalan village fresh water, and able to increase the income of the Morocalan Village community.